Pengaruh Content Creator TikTok @vmuliana Terhadap Pemenuhan Kebutuhan Informasi Seputar Dunia Kerja Di Kalangan Followers - Rieke Eva Kusumaningtyas; Rumyeni Rumyeni (KOLONI, 2022)
TikTok social media is one of application short video format completed with features to create content. It makes TikTok mostly used not only as a place to watch but also to spread various informations through contents by its user. One of informations spread through TikTok itself is the information about work wold. Recently also appears the account which particularly produces informatin about work world such a @vmuliana. The presence of @vmuliana creator eases the followers to obtain information about work world they need. This research aimed to measure the presence of @vmuliana content creator in fulfilling the need of its followers about the work world information. The main research instrument in this quantitative research was in the form of questionnaire spread to 400 respondents. SPSS software was employed to analyze the data. Linear regression analysis and determinant test were employed to find out if there was significant influence or not. The research results showed that the content creators gave influence in the amount of 51,1% in fulfilling the need of information about work world which means it was in the interval range with medium influence. Keywords: TikTok, World of Work Information, @vmuliana